Pengaruh Corporate Social Responsibility dan Good Corporate Governance Terhadap Kinerja Keuangan Pada Perusahaan Sub Sektor Rokok yang Terdaftar di Bursa Efek Indonesia - Lengkong, Fairy Lucia; Johny Manaroinsong; Meidy S.S. Kantohe (Universitas Muhammadiyah Gresik, 2025)
This study aims to determine the effect of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on the financial performance of cigarette companies listed on the Indonesia Stock Exchange. Through quantitative analysis of data from 2016 to 2023, this study reveals that CSR has a positive and significant effect on Return on Assets (ROA), while the influence of the Audit Committee does not affect ROA. Simultaneously, CSR and the Audit Committee affect ROA. The combined impact of CSR and the Audit Committee contributes around 26.97% to the company's financial performance. This study underlines the importance of CSR in improving financial results, although there is no substantial evidence to support the role of the Audit Committee in this regard. Keywords: Corporate Social Responsibbility; Audit Committee; Return On Assets